2016
DOI: 10.1038/cr.2016.53
|View full text |Cite
|
Sign up to set email alerts
|

Reversing drug resistance of soft tumor-repopulating cells by tumor cell-derived chemotherapeutic microparticles

Abstract: Developing novel approaches to reverse the drug resistance of tumor-repopulating cells (TRCs) or stem cell-like cancer cells is an urgent clinical need to improve outcomes of cancer patients. Here we show an innovative approach that reverses drug resistance of TRCs using tumor cell-derived microparticles (T-MPs) containing anti-tumor drugs. TRCs, by virtue of being more deformable than differentiated cancer cells, preferentially take up T-MPs that release anti-tumor drugs after entering cells, which in turn le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
229
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 201 publications
(233 citation statements)
references
References 42 publications
4
229
0
Order By: Relevance
“…Relative to differentiated tumor cells, drug-packaging T-MPs are more partial to attacking stem-like TRCs as they are softer than differentiated tumor cells and easier to deform when taking up T-MPs. 17 These TRCs were generated by the previously reported soft 3D fibrin gel method. 5 About 1,250 tumor cells were mixed with 125 mL fibrinogen solution (2 mg/mL fibrinogen, activated by 0.5 units of thrombin) and seeded on 24-well plate.…”
Section: Remodeling Macrophages By Combined Ldi and Cis-mps Is Explaimentioning
confidence: 99%
See 1 more Smart Citation
“…Relative to differentiated tumor cells, drug-packaging T-MPs are more partial to attacking stem-like TRCs as they are softer than differentiated tumor cells and easier to deform when taking up T-MPs. 17 These TRCs were generated by the previously reported soft 3D fibrin gel method. 5 About 1,250 tumor cells were mixed with 125 mL fibrinogen solution (2 mg/mL fibrinogen, activated by 0.5 units of thrombin) and seeded on 24-well plate.…”
Section: Remodeling Macrophages By Combined Ldi and Cis-mps Is Explaimentioning
confidence: 99%
“…14 Such specialized subcellular vesicles with 0.1-1 mm sizes are called microparticles (MPs). Recently, we have demonstrated that tumor cell-derived MPs (T-MPs) are capable of delivering chemotherapeutic drugs or oncolytic adenoviruses to nuclei of TRCs and disrupting them through a lysosomemediated pathway, [15][16][17][18][19] suggesting that drug-packaging MPs might be a potential means to improve antitumor immunity by abrogating TRCs. However, whether such drug-packaging MP-based approach of targeting TRCs can be strengthened by other means is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…The findings by Ma and colleagues [10] open the door to a new potential therapeutic approach that takes advantage of the mechanical changes that accompany carcinogenesis. Whether solid tumors can be targeted in this manner by intravenous injection of MPs in human patients, and which types of cancers are susceptible, are important questions for further study.…”
mentioning
confidence: 99%
“…In this manner, the death of cancer cells that ingest MPs, perhaps proximal to tumor vasculature that is sufficiently leaky, could spread to others not initially reached by intravenous delivery. Like a domino, the first cell to fall could trigger a therapeutic chain reaction that eliminates cancer (Figure 1) potentially due to effects on drug transporter expression or nuclear entry [10]. Whether the cellular origin, lipid content, or otherwise specific composition of MPs is important for their cytotoxic effects will be interesting to examine in future studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation